A New Species of Fritziana Mello-Leitao 1937 (Amphibia: Anura: Hemiphractidae) from the Atlantic Forest, Brazil - Walker, Marina [UNESP]; Wachlevski, Milena; Nogueira-Costa, Paulo; Garcia, Paulo C. A.; Haddad, Cello F. B. [UNESP] (Herpetologists League, 2018)
We describe a new species of the genus Fritziana, historically identified as Fritziana fissilis or F. aft fassilis. Using adult and tadpole morphology, as well as molecular analyses, we found the new species to be characterized by having the following traits: a mucronate snout tip, a black stripe on the wrist, round subarticular tubercles on the fingers and toes, a closed dorsal egg-pouch in females, tadpoles deposited in bromeliads, and a different mitochondria' transfer RNA gene order, when compared to the general orders already recognized for anurans. This new species occurs in the Atlantic Forest of Brazil, in the states of Sao Paulo, Parana, Santa Catarina, and Rio Grande do Sul, and has the largest geographic distribution recorded for a species of Fritziana.
Keywords: Egg-brooding frogs; Hemiphractinae; Mitochondria' tRNA; Gene order; Morphometrics; Tadpoles